Relationship Between Seed Maturity and Seed Dormancy In Acer Buergerianum Miq. (Bangladesh Journal of Botany, 2024)
Seeds are fundamental to plant survival and dispersal, yet their development and germination are influenced by various internal and external influences. There is little known about seed maturity and seed dormancy in Acer buergerianum. So, we investigated the relationship between seed maturity and seed dormancy through assessments of seed moisture content and various germination tests. The results showed that: 1. The water content in A. buergerianum seeds decreases as they mature. 2. Elevated seed maturity is linked to increased dormancy depth. 3. A. buergerianum seeds exhibit physiological dormancy. 4. Stratification can effectively release dormancy in A. buergerianum seeds. Understanding the dynamics between seed water content, maturity, and dormancy is pivotal for seed germination and seed propagation in Acer species.Bangladesh J. Bot. 53(2): 353-359, 2024 (June)